Bicycle commuting - Heinen, Eva, 1981- (Sustainable urban areas, 2011)
"Cycling is cheaper, healthier and in urban environments often faster than other transport modes. Nevertheless, even at short distances, many individuals do not cycle. This thesis aims to explain why commuters vary in their decision to bicycle. Results indicate that the individual (day-to-day) choice to commute by bicycle is affected by personal attitudes towards cycling to work, social norms, work situation, weather conditions and trip characteristics. Additionally, this thesis provides evidence that different groups of bicycle commuters exist: non-cyclists, part-time cyclists and full-time cyclists. The mode choice of individuals within these groups (partly) depends on a number of different factors. Non-cyclists seem not to cycle because they consider it impossible, either due to the distance involved, their need to transport goods, the need for a car during office hours, or a negative subjective norm. The decision to cycle among part-time or full-time cyclists is also affected by these factors, but additional factors can be identified. Finally, the day-to-day choice to cycle is based on work characteristics, weather conditions and trip characteristics. Part-time cyclists who cycle only occasionally are encouraged by pleasant weather conditions, while frequent cyclists are found to be discouraged by more practical barriers, such as where they need to work on that day"--Provided by publisher